The multiomics analyses of cancer stem cells isolated from solid tumors can provide insight for their immunological characterization. - Neha Gopinath (15431052) (2023)
Poster by  Neha Gopinath (Sidra Medicine),  Ishita Gupta (Sidra Medicine), Alice Turdo (Sidra Medicine), Rebecca Mathew (Sidra Medicine), Harshitha Shobha Manjunath (Sidra Medicine), Mohammed Toufiq (Sidra Medicine), Ola Hussein (Sidra Medicine),  Evonne Chin-Smith (Sidra Medicine), Matilde Todaro (Sidra Medicine), Giorgio Stassi (University of Palermo), Sara Tomei (Sidra Medicine), Ira Skvortsova (Medical University of Innsbruck and Tyrolean Cancer Research Institute), Soldano Ferrone (Harvard Medical School), Cristina Maccalli (Sidra Medicine) Background: Cancer stem cells (CSCs) represent a rare subpopulation of cells within the tumor that are considered responsible of metastatization and resistance to therapies, including immunotherapy. Objective: The aim of this study is to identify the molecular mechanisms regulating the immunological properties of cancer stem cells (CSCs) isolated from colorectal cancer (CRC) and breast cancer (BC) using integrative approaches including flow cytometry, miRNAs and RNA seq-based transcriptomic profile and in vitro functional assays. Methods: Colorectal cancer (CRC; N=15) and breast cancer (BC; N=21) cell lines, including differentiated tumor cells and CSCs, and, for BC, selected in vitro for radioresistance or invasiveness were used for this study. The baseline expression of HLA molecules and the components involved in the antigen processing machinery (APM) following or not the treatment with immunomodulatory or epigenetic agents was assessed through flow cytometry. Tumor cells were co-cultured with HLA-matched peripheral blood mononuclear cells (PBMCs) isolated from healthy donors to assess the efficiency of the CRC and BC cells endowed with stemness properties to elicit antigen-specific T cell responses.  The nCounter platform (Nanostring) was utilized to assess the hybridization with 800 probes for miRNAs and the RNA seq-based transcriptomic profile (Lexogen) was also assessed. Results: A general impairment of the expression of HLA and APM molecules was observed in CRC and BC lines. The down-modulation of the expression of HLA and APM was superior in “stem-like” cells as compared to the differentiated tumor cells. The treatment of these cells with immunomodulating or epigenetic agents could only partially restore the expression of these molecules. The induction in vitro of anti-tumor T cell responses through the co-culture of tumor cells with PBMCs, was associated with the levels of the expression HLA and APM molecules by the tumor cells and on the efficiency of their up-modulation by either immunomodulating or epigenetic agents. Differential miRNA profiles (p<0.05) were identified in either CRC or BC cells with stemness properties vs. differentiated cells, and in different subtypes of cells. Primary analysis of the significantly expressed miRNAs have identified target genes and their regulators involved in immune related pathways. Conclusion: The multiomics analyses of CSCs or stem-like cancer cells can identify immunological and gene signatures associated with the biological properties of the cells and  their susceptibility to immunotherapy.